Pre-service Home Economics Teachers’ Attitudes on Selected Aspects of Practical Teaching - Francka Lovšin Kozina (Center for Educational Policy Studies Journal, 2016)
This paper presents the results of a study conducted among pre-service home economics teachers from the Faculty of Education of the University of Ljubljana with different levels of practical experience in teaching. The pre-service Home Economics teachers in the 3rd year of their studies had just completed their first class of teaching experience in contrast to the pre-service teachers from the 4th year of their faculty studies, who had conducted more teaching lessons. The results showed that the 4th-year pre-service teachers had fewer doubts and problems concerning the planning and conducting of a lesson. They also statistically significantly agreed that they are sufficiently prepared to teach than the 3rd-year pre-service teachers are. The results showed that the majority of the pre-service teachers agreed that the feedback from their colleagues was helpful for their professional development. The results suggest the importance of practical teaching experience in the context of professional development and the intention to continue a career in education. However, the results also revealed some critical points in the teacher’s development of competency. The results suggest problems related to the application of theoretical knowledge on the children’s development in practice and problems related to classroom management in specific situations.